Ostani doma, migaj doma - Istenič, Nina (Šport (Ljubljana), 2021)
Regular physical activity can help with prevention and also management of chronical disease while modern sedentary lifestyle is one of the major risk factors for development of chronic disease. Family medicine practice Arcus Medici, Žiri, puts a special emphasis on the preventive medicine and especially physical fitness. Patients with low levels of physical fitness and/or chronical disease or other risk factors can be redered to a 6-months therapeutic exercise program. During coronavirus epidemic in spring of 2020 when it was not possible to hold live exercise classes for a 2-moths period they were substituted with online exercise videos. A series of online exercise videos were made for different age groups (children and adolescents, adults, seniors). Exercise videos for children and adolescents had the longest total watch time and the highest number of views. This indicates the importance of school PE classes and PE teachers in the field of promoting physical activity. Also exercise videos for adults (therapeutic exercise) and seniors had a significant number of views, especially considering that using ICT for this populations can be more challenging compared with younger ones. Patients who were a part of therapeutic exercise program in the season of 2019/20 have showed improvements in the fields of physical fitness (aerobic fitness, arms and legs strength endurance) and body composition (visceral fat area) even with 2-months online video program instead of live exercise classes. The analysis indicates that online exercise programs can be a usefull addition to other means of physical activity among the Slovenian people, especially in the times of exceptional circumstances (epidemic, natural disasters ...). Besides that, they can present a good and less time consuming way for people to be physically active in the privacy of their own home.
Keywords: COVID-19; družinska medicina; epidemic; epidemije; family medicine; ICT; IKT; kinesiology; kineziologija; physical activity; preventive healthcare; preventivno zdravstvo; sport; šport; telesna dejavnost; video exercise programs; videovadbe